1997
DOI: 10.1183/09031936.97.10081809
|View full text |Cite
|
Sign up to set email alerts
|

Do sputum eosinophils and ECP relate to the severity of asthma?

Abstract: There is much evidence that eosinophils play an important role in bronchial epithelial damage in asthma by releasing cationic proteins. However, the extent to which eosinophil inflammation relates to indices of asthma severity in chronic stable asthma is still a matter of debate.We studied 46 clinically stable patients with mild to severe chronic asthma (forced expiratory volume in one second (FEV1) 50-126% of predicted value). The clinical severity of asthma was graded from 1 to 4 according to the Aas scoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
49
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 31 publications
13
49
0
Order By: Relevance
“…29 Moreover, sputum examination has been demonstrated to be a more accurate diagnostic test than measurement of blood eosinophils or serum ECP in detecting airway eosinophilic inflammation, 29 suggesting a relevant role of sputum analysis in the identification and monitoring of airway inflammation in asthma. 12,14,30 Our results demonstrate that sputum eosinophils and ECP provide another unique dimension related to the status of patients with chronic bronchial asthma that was independent of both lung function and baseline BHR. These data confirm the results of previous studies in which the relationships between sputum outcomes and baseline airway obstruction were not clinically meaningful.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…29 Moreover, sputum examination has been demonstrated to be a more accurate diagnostic test than measurement of blood eosinophils or serum ECP in detecting airway eosinophilic inflammation, 29 suggesting a relevant role of sputum analysis in the identification and monitoring of airway inflammation in asthma. 12,14,30 Our results demonstrate that sputum eosinophils and ECP provide another unique dimension related to the status of patients with chronic bronchial asthma that was independent of both lung function and baseline BHR. These data confirm the results of previous studies in which the relationships between sputum outcomes and baseline airway obstruction were not clinically meaningful.…”
Section: Discussionmentioning
confidence: 63%
“…These data confirm the results of previous studies in which the relationships between sputum outcomes and baseline airway obstruction were not clinically meaningful. 12 Recent studies have found a relatively good correlation between sputum eosinophils and BHR when both normal subjects and smokers with bronchitis 13 or patients with rhinitis 31 were included in the correlation. Pizzichini et al 13 argue that the high significance of the correlations between sputum markers and hyperresponsiveness partially reflects the significant differences between asthmatic and healthy subjects or smokers with bronchitis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations